Where they stand : the American presidents in the eyes of voters and historians - Merry, Robert W., frey50 (Waterville, Me. : Thorndike Press, 2012)
For the 2012 presidential race, the author of the acclaimed biography of President James Polk offers a fresh, playful, and challenging way of playing "Rating the Presidents" - America's favorite game - by pitching historians' views and subsequent experts' polls against the judgment and votes of the presidents' own contemporaries. This voyage through all our history provides a sometimes surprising analysis of how presidential politics works.
Pt. 1. The historians. The judgment of history ; The vagaries of history -- pt. 2. The people. The making of the presidency ; The presidential referendum ; The judgment of the electorate ; The stain of failure -- pt. 3. The test of greatness. War and peace ; Split-decision presidents ; Leaders of destiny -- pt. 4. Reputations in flux. Republican resurgence ; The post-cold war presidents. Clear and present danger.
"Published in 2012 by arrangement with Simon & Schuster, Inc."--T.p. verso.
Keywords: Presidents -- Rating of -- United States; Presidents -- United States; Presidents -- United States -- History; Political leadership -- United States -- History; United States -- Politics and government